Iron fortification on shrikhand using Murraya koenigii leaves extract - Alan Jerish, J; Gnanalaksshmi, KS; Vijayarani, K; Manikkavasagan, I (Indian Journal of Dairy Science, 2020)
In the present study, a novel shrikhand enriched with vitamin C and iron was developed using curry leaves extract. Encapsulation, which is the latest trend in delivering the phytochemicals through food products has increased the acceptability of the product. The treatment S3which had the curry leaves extract of highest concentration 3:10 W/V had a good score on sensory evaluation due to the wall material - sodium alginate which acted as a barrier between the product and the extract without influencing the shrikhand with its strong off-flavor. The nutrient composition of shrikhand for energy, carbohydrate, fat, protein, moisture and ash was 199.65 Kcal, 23.67 g, 9.62 g, 4.55 g, 61.26 g and 0.85 g per 100 g of the product respectively. It was observed that the vitamin C and iron content was of 18.86 mg/100g and 2.26 mg/100g.